Thrombomodulin, Plasminogen Activator Inhibitor-1 and Protein C Levels, and Organ Dysfunction in Sepsis. (May 2019) - Katayama, Shinshu; Koyama, Kansuke; Shima, Jun; Tonai, Ken; Goto, Yuya; Koinuma, Toshitaka; Nunomiya, Shin
Abstract : Objectives: Since endothelial function is closely related to organ dysfunction in sepsis and the relationship among endothelial injury, organ dysfunction, and other biomarkers remains unclear, we aimed to evaluate the correlation among endothelial injury, organ dysfunction, and several biomarkers in patients with sepsis. Design: This was a retrospective observational study. Setting: The study was conducted in a university hospital with 14 mixed ICU beds. Patients: ICU patients with sepsis from June 2011 to December 2017 were enrolled in this study. Interventions: Endothelial biomarkers (soluble thrombomodulin, plasminogen activator inhibitor-1, and protein C) and markers of inflammation and coagulation were evaluated during the ICU stay. Sequential Organ Failure Assessment scores were assessed for 7 days after ICU admission to determine organ dysfunction. Variables were compared among five stratified groups according to the Sequential Organ Failure Assessment score (0–2, 3–5, 6–8, 9–12, and 13–24). Regression analysis and 95% CIs were used to evaluate trends in biomarkers. Measurements and Main Results: The patients were divided into five stratified groups (Sequential Organ Failure Assessment 0–2, n = 159 [20.5%]; Sequential Organ Failure Assessment 3–5, n = 296 [38.2%]; Sequential Organ Failure Assessment 6–8, n = 182 [23.5%]; Sequential Organ Failure Assessment 9–12, n = 75 [9.7%]; Sequential Organ Failure Assessment 13–24, n = 31 [4.0%]). Protein C activity was significantly correlated with the severity of organ dysfunction. It was lower on day 1, increased upon successful treatment, and was significantly higher in groups with lower Sequential Organ Failure Assessment scores. Conclusions: Trends and activity of protein C were superior in predicting organ dysfunction compared with other endothelial biomarkers. Monitoring the level of protein C activity is an ideal tool to monitor organ dysfunctions in patients with sepsis. Abstract : Supplemental Digital Content is available in the text.